Considering the safety of embryonic stem cells for medical use while ignoring any ethical concerns: a review - Al-Agele, Ramzi Abdulghafoor Abood (Diyala Journal for Veterinary Sciences, 2023)
The use of human embryonic stem cells has been the subject of growing amounts of legitimate research in recent years. Yet, the morality of these investigations is contested by a variety of current arguments in legal and ethical philosophy due to the harvesting of stem cells from the non-implanted fetus. This review focuses on one side of the issue, namely the therapeutic value of these cells, and glosses over the other sides, which include concerns about ethics and patient safety. It makes the case for evaluating embryonic stem cells as a way to rethink how we treat some of humanity's most intractable ailments. Yet, patient safety remains a challenge for this emerging biotechnology and the ethical and public policy implications of this need tobe carefully considered. The perennial conflicts over the moral validity of embryonic life may be lessened if researchers explored different approaches. Consequently, the issue may be resolved by extensive scientific study in the future with appropriate clinical applications.